5760000=x*(x+50)

Simple and best practice solution for 5760000=x*(x+50) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5760000=x*(x+50) equation:


Simplifying
5760000 = x(x + 50)

Reorder the terms:
5760000 = x(50 + x)
5760000 = (50 * x + x * x)
5760000 = (50x + x2)

Solving
5760000 = 50x + x2

Solving for variable 'x'.

Reorder the terms:
5760000 + -50x + -1x2 = 50x + -50x + x2 + -1x2

Combine like terms: 50x + -50x = 0
5760000 + -50x + -1x2 = 0 + x2 + -1x2
5760000 + -50x + -1x2 = x2 + -1x2

Combine like terms: x2 + -1x2 = 0
5760000 + -50x + -1x2 = 0

Begin completing the square.  Divide all terms by
-1 the coefficient of the squared term: 

Divide each side by '-1'.
-5760000 + 50x + x2 = 0

Move the constant term to the right:

Add '5760000' to each side of the equation.
-5760000 + 50x + 5760000 + x2 = 0 + 5760000

Reorder the terms:
-5760000 + 5760000 + 50x + x2 = 0 + 5760000

Combine like terms: -5760000 + 5760000 = 0
0 + 50x + x2 = 0 + 5760000
50x + x2 = 0 + 5760000

Combine like terms: 0 + 5760000 = 5760000
50x + x2 = 5760000

The x term is 50x.  Take half its coefficient (25).
Square it (625) and add it to both sides.

Add '625' to each side of the equation.
50x + 625 + x2 = 5760000 + 625

Reorder the terms:
625 + 50x + x2 = 5760000 + 625

Combine like terms: 5760000 + 625 = 5760625
625 + 50x + x2 = 5760625

Factor a perfect square on the left side:
(x + 25)(x + 25) = 5760625

Calculate the square root of the right side: 2400.130204801

Break this problem into two subproblems by setting 
(x + 25) equal to 2400.130204801 and -2400.130204801.

Subproblem 1

x + 25 = 2400.130204801 Simplifying x + 25 = 2400.130204801 Reorder the terms: 25 + x = 2400.130204801 Solving 25 + x = 2400.130204801 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + x = 2400.130204801 + -25 Combine like terms: 25 + -25 = 0 0 + x = 2400.130204801 + -25 x = 2400.130204801 + -25 Combine like terms: 2400.130204801 + -25 = 2375.130204801 x = 2375.130204801 Simplifying x = 2375.130204801

Subproblem 2

x + 25 = -2400.130204801 Simplifying x + 25 = -2400.130204801 Reorder the terms: 25 + x = -2400.130204801 Solving 25 + x = -2400.130204801 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + x = -2400.130204801 + -25 Combine like terms: 25 + -25 = 0 0 + x = -2400.130204801 + -25 x = -2400.130204801 + -25 Combine like terms: -2400.130204801 + -25 = -2425.130204801 x = -2425.130204801 Simplifying x = -2425.130204801

Solution

The solution to the problem is based on the solutions from the subproblems. x = {2375.130204801, -2425.130204801}

See similar equations:

| 4w-4=2w-11 | | 6.6+6n=7n-0.4 | | 2x+1=x+37 | | -104=8i | | 30x+(20-x)x=100 | | h-9=-13 | | f(x)=-1.5x+10 | | 4.5(7)+4.5(6)= | | -20=-4e-6e | | 270+230+240+250= | | 101.75*3.65= | | -8t=32 | | J-15=-27 | | 2x+5=10.50 | | 5x-15=-7+7x | | 8z-17=-59+z | | 125t=0 | | N-.5=10 | | 19x^2+38x+1=0 | | -3(t-2)+5t=7t-7 | | 1-3x=12x-6 | | -14x-9=201 | | 6cosx+6secx=13 | | -11x+14=129 | | -3x-20=155 | | =5x-1 | | 11x+9=3x-2 | | 6(3n-4)=(7n+9)+2 | | (9x-9)=(4x+16) | | 3x-3x+12=12 | | 13+3=81 | | x+3.5=25 |

Equations solver categories